RAGAM PENERJEMAHAN HURUF JAR MIN DALAM “QUR’AN KARIM DAN TERJEMAHAN ARTINYA” TERBITAN UII: Studi pada Surah al-Baqarah - Kholifah, Nurul (AL ITQAN: Jurnal Studi Al-Qur'an, 2022)
This study aims to determine the meanings of the min preposition Q.S al-Baqarah in "Qur`an Karim dan Terjemahan Artinya" published by UII. This research is a qualitative research with the type of library research. Then, the data collection uses the documentation method by reviewing books, literature, notes or reports related to the problem being studied. As for the results of the research in Q.S al-Baqarah verses 91-126, the authors found 22 verses with the mention of the min preposition 36 times which are divided into six meanings, each meaning is as follows; the min preposition on the meaning of al-ibtidā` was found 9 times, the meaning of al-tab'īd 8 times, the meaning of al-bayān 3 times, the meaning of al-ta'kīd 7 times, the meaning of al-badal 3 times, and the meaning of al-ẓarfiyah 6 times. The translation of the meanings of the min preposition is closely related to the construction and context of the sentence because the min preposition does not only have a lexical meaning but also a grammatical meaning.